(untitled) (Research, Society and Development, 2020)
Objective: To assess dental anxiety in patients undergoing oral surgery, as well as its impact on blood pressure and heart rate. Material and Methods: A total of 233 patients answered a socio-demographic questionnaire and another one based on the Corah dental anxiety scale. Blood pressure and heart rate were assessed at three moments while: patients were in the waiting room, immediately before and after the procedure. Results: This study revealed a prevalence of anxiety of 77.3%. There was a statistically significant difference in mean systolic blood pressure and heart rate at the three moments of the evaluation. Anxiety was prevalent in the sample and was observed from the time in the waiting room until the time when local anesthesia was performed, causing variations in systolic blood pressure and heart rate, anxiety levels decreased after the end of the service. In conclusion, we observed that oral surgery is directly related to increased anxiety, and anxiety is mainly related to the change in heart rate.